2013
DOI: 10.2460/javma.242.10.1364
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term outcomes for overweight dogs with cranial cruciate ligament rupture treated surgically or nonsurgically

Abstract: Overweight dogs with CCLR treated via surgical and nonsurgical methods had better outcomes than dogs treated via nonsurgical methods alone. However, almost two-thirds of the dogs in the nonsurgical treatment group had a successful outcome at the 52-week evaluation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
2
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 28 publications
3
63
2
5
Order By: Relevance
“…The (6). Future study should assess the outcome and level of return to function of patients with cranial cruciate ligament insufficiency treated with rehabilitation therapy and a custom stifle orthotic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The (6). Future study should assess the outcome and level of return to function of patients with cranial cruciate ligament insufficiency treated with rehabilitation therapy and a custom stifle orthotic.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have shown surgical stabilization to be effective in managing cranial cruciate ligament insufficiency (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). While there are numerous options for surgical management, surgery is not always an option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment involves surgical joint stabilization and the medical management of pain and inflammation. To restore joint stability, tibial plateau leveling osteotomy (TPLO) is one of the most common surgical procedures performed worldwide (46), delivering quick and good clinical outcomes for a majority of the treated dogs (711). The biomechanical purpose of TPLO is to decrease the tibial slope angle through radial proximal tibial osteotomy, so the joint stability during gait no longer relies on the integrity of the cranial cruciate ligament.…”
Section: Introductionmentioning
confidence: 99%
“…Immediate postoperative management includes non-steroidal anti-inflammatory drugs (NSAIDs) to alleviate pain and inflammation resulting from both preoperative CrCLR-related arthritis and the surgical procedure (11, 12). …”
Section: Introductionmentioning
confidence: 99%